A Case Study of the “San Giovanni Di Dio E Ruggi D’aragona” Aou on Acceptance or Hesitancy to the Covid-19 Vaccination Campaign, after the Introduction of the Green Digital Pass - G. Cersosimo; G. Moccia (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
We aim to articulate the relationships between people's behavior and their vaccination representations according to social characteristics and the role of social media. We conducted our research using questionnaires and content analysis of magazines. Our work underscores how the interconnection among representations, people, experience, doubts about science, and many reiterated ambivalent messages of the media, trigger contradictory positions in most cases. Compared to this, a sociological approach may be useful for identifying the social conditions under which skeptical attitudes towards vaccinations emerge.